Impact of Agricultural and Environmental Policies in Latin America and Caribbean - Jaslin U. Salmon Ph.D. (My University, 2016)
Document was produced to provide a possible solution that would pursue social social and economic development in Latin America and the Caribbean without jeopardizing future generation by requiring specific policies or commitments by the government.